Responsive Regulation for Non-platform Media: Challenges and Opportunities in Indonesia - Abie Besman; Inne Nathalia; Firdza Radiany (Universitas Multimedia Nusantara, 2023)
This research investigates the regulation of non-platform media in Indonesia from a legal perspective. Non-platform media, such as social media, blogs, and personal websites, have become influential communication tools in modern society. The study explores various relevant aspects, including freedom of speech, inequality in access, ethics, international cooperation, and the role of the government. The research employs a qualitative approach, allowing for a deep understanding of the non-platform media phenomenon. The literature review is used to construct a framework of relevant theories and concepts related to the research topic and to identify current research trends in the context of non-platform media. The objective of this research is to comprehend how the Indonesian government regulates non-platform media with the existing rules and regulations and its impact on the media industry and the public. Using a qualitative approach, this research aims to provide in-depth insights into the complex debate surrounding the regulation of non-platform media in Indonesia and how these regulations can achieve a balance between freedom of speech and the protection of the public.